4D Printing Technology: A Review - Choi, Jin; Kwon, O-Chang; Jo, Wonjin; Lee, Heon Ju; Moon, Myoung-Woon (MARY ANN LIEBERT, INC, 2015)
3D printing has been recognized as a disruptive technology for future advanced manufacturing systems. With a great potential to change everything from our daily lives to the global economy, significant advances in 3D printing technology have been made with respect to materials, printers, and processes. In this context, although similar to 3D printing technology, 4D printing technology adds the fourth dimension of time. 4D printing allows a printed structure to change its form or function with time in response to stimuli such as pressure, temperature, wind, water, and light. Recently, rapid advances in printing processes and materials development for 3D printing have allowed the printing of smart materials or multimaterials designed to change function or shape. In this review, we first compare the similarities and differences between 3D printing and 4D printing. We then look into the main factors composing 4D printing technology such as smart materials and designs. Finally, we summarize the current applications of 4D printing.
Keywords: 3D; MULTIMATERIAL; SCAFFOLDS; DESIGN